STUDI PASANGAN CCSP UNTUK PERKUATAN TANGGUL PADA PROYEK RENTANG IRRIGATION MODERNIZATION PROJECT - Wahaerudin, Heru; Kholiq, Abdul (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
An Irrigated Area is a unit of land that gets water from an irrigation network. Irrigation Networks are channels, buildings, and their complementary buildings that are a single entity necessary for the provision, division, administration, use and disposal of irrigation. The Range Irrigation Area is located in the lowlands of the lower reaches of the Cimanuk river in the northern part of Majalengka Regency from West Java Province. Irrigation Modernization This range is carried out because the irrigation system has not been modernized for decades, causing the performance of water services to be less than optimal. The use of materials for construction that is in the ground or groundwater level, namely by using Corrugated Concrete Sheet Pile (CCSP), Corrugated Concrete Sheet Pile (CCSP) is a concrete used for foundation structures or irrigation canals that function as soil retaining walls. Corrugated Concrete Sheet Pile (CCSP) is one of the products owned by a well-known concrete company, namely WIKA concrete. The type of CCSP used in this project is CCSP W325 B with a length of 9 meters. There are 3 stages of work regarding the Method of Implementing Corrugated Concrete Sheet Pile Pairs, starting from the Preparation, Erection of Corrugated Concrete Sheet Pile, Capping Beam Work.